Age related clinical features of childhood Coeliac disease in Australia - Whitten Kylie E; Bohane Timothy D; Stone Monique L; Tobias Vivienne H; Day Andrew S (BMC, 2005)
Abstract Background To describe the presenting clinical features of coeliac disease in a single paediatric centre, and to determine if the presenting features vary with age. Methods A review was conducted of children who had been referred with clinical suspicion of coeliac disease to the paediatric gastroenterology department of a tertiary paediatric hospital in Sydney, Australia. Coeliac disease was defined using standard histological criteria. Medical records were reviewed retrospectively. Results Clinical data were available for 74 cases of proven coeliac disease. Only 9% of patients were less than 2 years of age at diagnosis. Pre-school children (age <5 years) presented with different symptoms to school children (age ≥ 5 years). The most common presenting features in younger children were diarrhoea, irritability and weight loss. However, in older children, abdominal pain was the most common presenting feature. Conclusion We found a significant difference in the clinical features of coeliac disease in pre-school compared to school age children.